2017
DOI: 10.1093/nar/gkx085
|View full text |Cite
|
Sign up to set email alerts
|

Natural antisense transcripts are significantly involved in regulation of drought stress in maize

Abstract: Natural antisense transcripts (NATs) are a prominent and complex class of regulatory RNAs. Using strand-specific RNA sequencing, we identified 1769 sense and antisense transcript pairs (NAT pairs) in two maize inbreds with different sensitivity to drought, as well as in two derivative recombination inbred lines (RILs). A significantly higher proportion of NATs relative to non-NATs are specifically expressed under water stress (WS). Surprisingly, expression of sense and antisense transcripts produced by NAT pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 98 publications
1
41
0
Order By: Relevance
“…More recently, the development of the next sequence generation technology and the gaining of knowledge on the gene silencing, contribute to change this opinion revealing that an extensive number of NATs have a functional role. NATs have been surveyed in Arabidopsis [108], rice [109], wheat [110] and several legumes [111] and involved in response of abiotic stresses [112,113] and developmental transitions [114][115][116]. The mechanism of action of NATs are still not fully understood [117], although in many cases their role is in the repression of their sense cognate transcripts [118].…”
Section: The Genetic Control Of Apomixismentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the development of the next sequence generation technology and the gaining of knowledge on the gene silencing, contribute to change this opinion revealing that an extensive number of NATs have a functional role. NATs have been surveyed in Arabidopsis [108], rice [109], wheat [110] and several legumes [111] and involved in response of abiotic stresses [112,113] and developmental transitions [114][115][116]. The mechanism of action of NATs are still not fully understood [117], although in many cases their role is in the repression of their sense cognate transcripts [118].…”
Section: The Genetic Control Of Apomixismentioning
confidence: 99%
“…Our findings show that apomixis-linked genes are expressed as sense and antisense transcripts in cell lineages of sexual ovules, whereas their expression of both transcripts was strongly down regulated in the same cells of apomictic ovules. Coordinated down or up regulation of both sense and antisense transcripts derived from NAT pairs has been reported under water stress conditions in maize [112], suggesting that "sexual" and "apomictic" alleles may interact each other as NAT gene pairs (i.e., gene pairs that express transcripts that are overlapping and complementary). The nature of this interaction is generally poorly understood, although a possible link between antisense transcripts and chromatin modification has been proposed [108,119].…”
Section: The Genetic Control Of Apomixismentioning
confidence: 99%
“…Among the transcripts clustered by WGCNA were lncRNAs. lncRNAs are proposed to function as gene expression regulators, particularly in organisms experiencing stress [36]. In this study, the two Eutrema salsugineum ecotypes display different transcriptional responses to water deficits.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study reported a method that was developed to express sgRNA with RNA polymerase II promoter by using self-cleaving ribozymes and tRNA 26 . In addition, sgRNA-shRNA structure has been also introduced to the multiplex genome engineering by using U6 promoter 27 .…”
Section: Discussionmentioning
confidence: 99%